Exploring Social Media Impact in Admission Campaigns. A Comparative Research - Alexandru GRIGORAS (Management Intercultural)
As universities face increasingly high competition to attract students, social media are becoming more and more important in communication campaigns. The article aims to investigate the role that social networks have in admissions campaigns, by conducting a comparative study on the two main target audiences: high school students - who will go through the admissions process in the future and can provide information to develop possible strategies for future communication campaigns, and undergraduate students, who have already experienced the admission process and find out how they evaluate the impact of social media. As a result, we can see the role social media play in admissions campaigns and plan strategic directions for future communication actions.